Perancangan Desain Interaksi Modul Informasi Kuliner Pada Aplikasi Malang Directory Dengan Metode Think Aloud - Agnes Kristianti Novilda; Herman Tolle; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Malang City wants to implement a smart city system by creating an integrated application, namely the Malang Directory application. In the Malang Directory application, there is a lot of info about Malang City. Such as public service info, education info, tourism info, health info, and culinary info. Existing culinary information is still not centralized, mobile applications are a solution that can unify existing information, and are easy to access. The design of interaction design on culinary information uses the Think Aloud method to get as much input from users as pre-existing applications. This research begins with a user needs analysis which produces a specification of user requirements that will be used for designing a solution design, then designing a solution design produces an interactive prototype for evaluation. The evaluation was carried out on 10 users and resulted in 98% effectiveness aspects, 98% efficiency aspects, and 78.5% user satisfaction aspects. The achieved usability value is 91.5% and it's in the very good category.